Tinea: Incidence during Magh Mela - Narain, Upma; Bajaj, Ashok Kumar; Kant, Arun (International Journal of Advances in Medicine, 2018)
Background: Dermatophytosis refer to superficial fungal infection of keratinized tissues caused by keratinophilic dermatophytes. It is common in tropics and may present in epidemic proportions in areas with high rates of humidity. Methods: The retrospective study was carried out from January 2018 to February 2018 at Allahabad. Gram stain, KOH examination and culture were carried out in 300 cases. Results: Out of the 300 suspected cases authors identified, 263 cultures tested positive. The macroscopic examination of the scalp, skin and the nails of these 36 patients further revealed 50.20% Tinea corporis, 17.87% Tinea cruris, 11.02 % Tinea mannum, 8.74% Tinea pedis, 7.99% onychomycosis, 3.42% Tinea versicolor and 0.76% Tinea capitis. Culture examinations revealed 52.47% Trychophyton mentagrophyte, 34.98% Trichyopyton rubrum, 3.80% Trychophyton violaceum, 3.43% Malessesia, 2.28% Scopulariopsis brevicaulis, 1.52% Trichophyton verrucosum, 0.76% Microsporum canis and 0.76% Epidermophyton flucossum. Conclusions: The study concludes that in a short period of Magh Mela authors got a large number of skin patients because of their belief that the holiness Ganga water will cure skin problems by itself. Some of the patients were found infected from the beginning and some gather infections during their stay in the mela period. Therefore, a prompt recognition of skin lesions and the identification of these superficial fungi are required for judicious management.